Pemikiran Ekonomi: Imam Al-Syaibani - Nisa Syahira Najla; Rizki Fauziyah Nasution; Radia Havni Sari Harahap; Ahmad Wahyudi Zein (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Imam al-Syaibani was an Islamic economic thinker who lived at the time of Abu Yusuf and was one of the pioneers in the spread and development of the Hanafi school of thought. Al-Syaibani's economic thinking can be seen in the Book of al-Kasb, al-lhtisab fi al-Rizq al-Mustahab, and the book of al-Asi which discusses income, guidelines for production and consumption behavior, various forms of business such as trade, agriculture, industry and employment agreement. Al-Syaibani's economic thinking in the current context is still very relevant, especially the concept of al-kasb which must refer to utility and benefit.